2022
DOI: 10.1021/acs.jnatprod.2c00830
|View full text |Cite
|
Sign up to set email alerts
|

Xylochemical Synthesis and Biological Evaluation of the Orchidaceous Natural Products Isoarundinin I, Bleochrin F, Blestanol K, and Pleionol

Abstract: The first total syntheses of the orchid-derived natural products isoarundinin I (1), (±)-bleochrin F ((±)-2), (±)-blestanol K ((±)-3), and (±)-pleionol ((±)-4) from renewable starting materials are reported, along with the evaluation of their biological activities. The total syntheses were based on regioselective aromatic bromination reactions in combination with a key acidpromoted regioselective intramolecular cyclization. The biological results suggest that isoarundinin I ( 1), (±)-blestanol K ((±)-3), and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…According to our findings, CEM/ADR5000 cells and their sensitive counterparts both demonstrated a similar level of sensitivity to adapalene. Furthermore, the resistance ratio was just 1.26, which is far lower than that of doxorubicin, a common chemotherapeutic medication with a cross-resistance ratio much more than 1000 [ 30 ]. These findings suggested that adapalene is not involved in the cross-resistance profile conferred by P-glycoprotein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our findings, CEM/ADR5000 cells and their sensitive counterparts both demonstrated a similar level of sensitivity to adapalene. Furthermore, the resistance ratio was just 1.26, which is far lower than that of doxorubicin, a common chemotherapeutic medication with a cross-resistance ratio much more than 1000 [ 30 ]. These findings suggested that adapalene is not involved in the cross-resistance profile conferred by P-glycoprotein.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of MM cells, leukemia cells, and PBMCs to adapalene was evaluated by the resazurin reduction assay, as previously described [ 30 ]. In brief, 10 4 cells were seeded in each well of a flat bottom 96-well plate.…”
Section: Methodsmentioning
confidence: 99%